Analisa Mampu Redam Suara Komposit Serat Sabut Kelapa Dengan Matriks Polyvinyl Acetate (Lem Fox) - Said, Harman; Mangalla, Lukas Kano; Sudia, Budiman (Teknik Mesin Universitas Halu Oleo, 2019)
This study aims to find out and analyze the ability of the sound attenuation of coco fiber composites with polyvinyl acetate (fox glue) matrix on various compositions. The composite material used is coconut fiber with polyvinyl acetate (Fox glue). The data obtained were tested using tube impedance along with speaker devices, amplifiers, power supplay, leptop / smartphone, oscilloscope, sound lever meter with input frequencies of 1000, 1500, 2000, and 2500 Hz. The results of the Noice Absorption Coefficient (NAC) value of the composite coir fiber test specimens with polyvinyl acetate matrix (Fox glue) have the highest sound absorption coefficient (α) 0.50788 at fiber volume fraction of 20%: 80% with a frequency of 2500 Hz. While for the lowest sound absorption results (α) 0.50121 with fiber volume fraction of 40%: 60% with a frequency of 1000 Hz. The results of all test specimens can be used as sound absorption material because it has a sound absorption coefficient > 0.5 and porous and fibrous. Keywords : Composite, Coconut Fiber, Polyvinyl Acetate (Fox Glue) And Noice Absorption Coeffisien